Primary angiocentric/angioinvasive T-cell lymphoma of the tympanic bulla in a feline leukaemia virus-positive cat - Sara F Santagostino; Carlo M Mortellaro; Julia Buchholz; Margherita Lugli; Annalisa Forlani; Gabriele Ghisleni; Paola Roccabianca (Journal of Feline Medicine and Surgery Open Reports, 2015)
Case summary A 5-year-old neutered female feline leukaemia virus (FeLV)-positive domestic shorthair cat with a 5 month history of otitis media was referred for head tilt, stertor and dyspnoea. Computed tomography scan revealed soft tissue opacities inside the right tympanic bulla, with bone remodelling, and concurrent nasopharyngeal and intracranial invasion. Endoscopically guided bioptic samples were collected from the nasopharynx and middle ear. Histology revealed dense sheets of round, large, neoplastic cells, often surrounding or invading vascular walls. Neoplastic cells expressed CD3, FeLV p27 and gp70 antigens. A middle ear angiocentric/angioinvasive T-cell lymphoma was diagnosed. After improvement of clinical conditions following radiation therapy, the cat died unexpectedly. At necropsy, hepatic and splenic spread was detected. Relevance and novel information Primary middle ear tumours are rare and their diagnosis is often delayed as clinical signs mimic more common otological conditions. Multiple bioptic specimens are pivotal for a definitive diagnosis. The young age of the cat, serology and immunohistochemistry revealed a possible transforming role of FeLV.